The association of relative humidity and air pollution interaction on lung function in adolescents - Areal, Ashtyn T.; Singh, Nidhi; Zhao, Qi; Berdel, Dietrich; Koletzko, Sibylle; von Berg, Andrea; Gappa, Monika; Heinrich, Joachim; Standl, Marie; Schikowski, Tamara (Frontiers in Environmental Health, 2023)
Background: Relative humidity (RH) and air pollution significantly affect respiratory health. However, how RH and air pollution interact and modify each other and affect lung function in adolescence is largely unknown. This study assesses the interactive effectassociation of RH and air pollution on lung function, i.e. forced vital capacity (FVC) and forced expiratory volume in one second (FEV1), in German adolescents.Methods: A total of 2116 participants with available spirometry measurements (z-scores of FEV1 and FVC) were included from the 15-year follow-up of the German GINIplus and LISA birth cohort. Daily environmental exposure data included RH, ozone (O3), nitrogen dioxide (NO2), and particulate matter <2.5µm (PM2.5). Linear models were fitted to assess the main effectassociations of RH, air pollution, and maximum temperature (Tmax)] an interaction term between one-day moving average of RH (Lag01) and a categorical air pollution term was then included to assess the modifying effectassociation of air pollution on RH and was adjusted for study location, season and chronic respiratory disease (CRD) status. Effect modification was performed for sex and CRD. The results are presented as beta coefficients (ß) and 95% confidence intervals (95%CI).Results: A 5% increase in RH was associated with an increase in FEV1 (ß= 0.040-0.045; 95%CI:0.008 to 0.076) and FVC (ß=0.007-0.012; 95%CI: -0.023 to 0.045) in the main effectassociations models. In the interaction models, there was a significant decrease in FEV1 (ß= -0.211; 95%CI: -0.361 to -0.062) and FVC (ß= -0.258; 95%CI: -0.403 to -0.0113) per 5% increase in RH on high O3 days compared to the reference category; while there was a non-significant trend towards a decrease in FEV1 on high PM2.5 and NO2 days. Female participants were more likely to experience a decrease in FEV1 than male participants on high-pollution days.Conclusions: Air pollution interacts and modifies the effectassociation of weather on lung function in this cohort of German adolescents. An increase in RH on high air pollution exposure days was associated with a decrease in lung function in German adolescents. Female participants were more sensitive to the effects of RH and air pollution.